Profiles, co-morbidity and their relationship to treatment of 191 children with AD/HD and their families. - Thompson MJJ; Brooke XM; West CA; Johnson HR; Bumby EJ; Brodrick P; Pepe G; Laver-Bradbury C; Scott N (European Child & Adolescent Psychiatry, 2004)
BACKGROUND: This study was set up to re-audit our use of a protocol for the assessment and treatment for children on psycho-stimulant medication within a community clinic for children with Attention Deficit/Hyperactive Disorder (AD/HD) and to examine the profile of children and their families referred to the clinic in order to consider their assessment and treatment needs. METHOD: A questionnaire based on results from previous studies was completed for 191 patients from a case note audit, and by questioning clinicians. Key areas examined were symptomatology and child and family variables, which included learning difficulties, medical problems, psychosocial factors and side-effects of medication. RESULTS: The protocol was used appropriately with the majority of children. Children with AD/HD referred to the clinic often presented with co-morbid psychopathology, e. g. conduct disorder, low self-esteem, and frequently experienced family and psychosocial difficulties. CONCLUSIONS: Protocols in clinics are useful as this should maintain good practice and allow on-going monitoring, but they need precise use. Also, as many children with AD/HD present with co-morbid psychopathology and complicated family dynamics to Child and Adolescent Mental Health Services, this will influence assessment and treatment needs and require increased resources.